Cry havoc : a novel - Wait, Rebecca (Harper Perennial, 2026)
"Fleeing Scotland after a humiliating family scandal, sixteen-year-old Ida Campbell secures a scholarship at a failing girls' boarding school situated on the remote south English coast. Her new Headmistress-an eccentric woman obsessed with the Cold War and nuclear annihilation-seems surprised that the young woman accepted her offer, but Ida feels that St. Anne's could be a refuge-until she discovers that her roommate, the infamous Louise Adler, is a potential arsonist and hardened outcast. Ida barely has time to make a good impression (or figure out what Louise's deal is) when Matthew Langfield, a new teacher, arrives. While the girls are all desperately intrigued to find out everything about him - after all, who takes a job at St. Anne's? - the school's geography teacher, Eleanor Alston, has an uneasy feeling that he is not who he says he is. And things only get worse when a mysterious sickness starts to spread throughout the school, causing strange limb jerks and seizures among the pupils. What is happening to the girls of St Anne's? Are some of the girls faking these fits? Could someone be poisoning them? Is Matthew Langfield a smooth-tongued liar? Will Louise set the school on fire, or push a girl out of a window. . . again? And is Ida's past going to catch up with her, despite doing everything to keep it secret?"-- Provided by publisher.